BEEF CATTLE INTEGRATION ON DRY-LAND FARMING IN SRAGEN CENTRAL-JAVA INDONESIA: IMPROVEMENTS OF ECONOMIC AND ENVIRONMENTAL CARRYING CAPACITY ASPECTS - Rahardjo, M; Suroyo, Suroyo (ANIMAL PRODUCTION, 2013)
This study aimed to investigate the impact of beef cattle integration on dry land farming of peanut and maize with a focus on the economic and the environmental carrying capacity aspects. The multiyears of field experiments were conducted on the Kebun Pengembangan Pertanian Terpadu, Lembaga Pendidikan Pelatihan dan Penelitian Wiyata Dharma located at Geneng Duwur Village, Gemolong Distrik, Sragen Regency, Central-Java Indonesia.  The experimental design was a randomized complete block with three replications. Six block combinations were implemented:  block 1 (no-beef cattle integration), block 2 (1-year beef cattle integration), block 3 (2-year beef cattle integration), block 4 (3-year beef cattle integration), block 5 (4-year beef cattle integration), and block 6 (5-year beef cattle integration). Spatial separated integration of beef cattle were implemented  on the peanut and maize crop of dryland farming. A major advantage of the integrated system of crop and beef cattle is that nutrients from the wastes can be recycled efficiently on the farm. The results showed that there was an increase in productivity and efficiency of farm enterprises, as well as an increase in the environment carrying capacity. The impact of beef cattle integration was that, it  improved the enterprises productivity (75%) of dryland farming  (during 5 years period) and created sustainable agriculture. In order to improve farmers? livelihoods and develop sustainable dry land farming systems, the changing of practical agriculture especially farmer in dry land areas for peanut and maize should receive more attention of researchers, government institutions and stakeholders.Animal Production 15(2):135-143, May 2013